ANALISIS PENGARUH PEMBERIAN KREDIT TERHADAP KEBERHASILAN USAHA - Namkatu, Darmin; Janwarin, Xaverius M; Tomasoa, Theodora F (Program Studi Akuntansi PSDKU Universitas Pattimura di Kabupaten Maluku Barat Daya, 2025)
This study aims to determine the effect of credit provision on business success (Case study of MSME customers made by PT. Pegadaian (Persero) passso branch). This type of data is collected after primary data and secondary data are collected from research activities. The data analysis method uses quantitative descriptive analysis method. Data collection techniques using saturated sampling by distributing questionnaires to customers. Our data analysis technique is validity test, reliability test, simple linear regression analysis with t test hypothesis test. Based on the results of research on the analysis of credit provision on business success (case study of PT Persero Pawnshop Passo Branch), it can be concluded that creative credit provision has a significant influence on business success. This is evident from the results of simple linear regression analysis resulting from the calculation of the t-statistic value of the t value> t table (16.326>0.6838) with a significant level of 0.000 <0.05 which means that Ha is accepted. This means that the loan variable has a significant influence on business success by 93.6% and the remaining 6.4% based on the interpretation of the r value coefficient (Alma, 2009; 81) shows that the relationship between lending and the business success of PT Pawnshop Passo Branch is a positive relationship.